The dynamics of population distributions in cities based on daily mobile phone operations: A case study of some Moravian cities - Kopáčik, Gabriel; Vaishar, Antonín; Šimara, Eva (ACAD SCI CZECH REPUBLIC, INST GEONICS, 2021)
Analyses of the changes in the presence of persons in different central and residential parts of urban areas are subject to evaluation in this paper. Case studies of the cities of Brno, Ostrava and Zlin during the day and night are highlighted. Data from a provider of mobile phone services were used for the analyses. It appears that the data can be important for the comparison of different urban structures. The results demonstrate that the organisation of urban structure affects the number of visitors and thus the area attractiveness. It was confirmed that the number of mobile phone users in the city cores is higher than the number of permanent residents. The greatest differences between the day and night in the city cores were found in Brno, a concentric city with the most important central functions among the cities studied. Differences between the day and night in residential areas were not as large as expected. City neighbourhoods in Brno showed some specific rhythmicity.

Analyses of the changes in the presence of persons in different central and residential parts of urban areas are subject to evaluation in this paper. Case studies of the cities of Brno, Ostrava and Zlin during the day and night are highlighted. Data from a provider of mobile phone services were used for the analyses. It appears that the data can be important for the comparison of different urban structures. The results demonstrate that the organisation of urban structure affects the number of visitors and thus the area attractiveness. It was confirmed that the number of mobile phone users in the city cores is higher than the number of permanent residents. The greatest differences between the day and night in the city cores were found in Brno, a concentric city with the most important central functions among the cities studied. Differences between the day and night in residential areas were not as large as expected. City neighbourhoods in Brno showed some specific rhythmicity.
The dynamics of population distributions in cities based on daily mobile phone operations: A case study of some Moravian cities
Keywords: day/night population dynamics; mobile services providers; urban structures; Brno; Ostrava; Zlin; Czech Republic; day/night population dynamics; mobile services providers; urban structures; Brno; Ostrava; Zlin; Czech Republic